Oral CBD-rich hemp extract modulates sterile inflammation in female and male rats - Hopkins, Shelby; Kelley, Tel; Roller, Rachel; Thompson, Robert S.; Colagiovanni, Dorothy B.; Chupka, Kris; Fleshner, Monika (Frontiers in Physiology, 2023)
Cannabidiol (CBD) extract from the cannabis plant has biomedical and nutraceutical potential. Unlike tetrahydrocannabinol (THC), CBD products produce few psychoactive effects and pose little risk for abuse. There is emerging preclinical and clinical evidence that CBD is stress-modulatory and may have anti-inflammatory properties. People across the United States legally ingest CBD-rich hemp extracts to manage mental and physical health problems, including stress and inflammation. Preclinical studies have revealed potential mechanisms for these effects; however, the impact of this prior work is diminished because many studies: 1) tested synthetic CBD rather than CBD-rich hemp extracts containing terpenes and/or other cannabinoids thought to enhance therapeutic benefits; 2) administered CBD via injection into the peritoneal cavity or the brain instead of oral ingestion; and 3) failed to examine potential sex differences. To address these gaps in the literature, the following study tested the hypothesis that the voluntary oral ingestion of CBD-rich hemp extract will attenuate the impact of stressor exposure on plasma and tissue inflammatory and stress proteins in females and males. Adult male and female Sprague Dawley rats (10-15/group) were randomly assigned to be given cereal coated with either vehicle (coconut oil) or CBD-rich hemp extract (L-M0717, CBDrx/Functional Remedies, 20.0 mg/kg). After seven days, rats were exposed to a well-established acute model of stress (100, 1.5mA, 5-s, intermittent tail shocks, 90 min total duration) or remained in home cages as non-stressed controls. Stressor exposure induced a robust stress response i.e., increased plasma corticosterone and blood glucose, and decreased spleen weight (a surrogate measure of sympathetic nervous system activation). Overall, stress-induced increases in inflammatory and stress proteins were lower in females than males, and oral CBD-rich hemp extract constrained these responses in adipose tissue (AT) and mesenteric lymph nodes (MLN). Consistent with previous reports, females had higher levels of stress-evoked corticosterone compared to males, which may have contributed to the constrained inflammatory response measured in females. Results from this study suggest that features of the acute stress response are impacted by oral ingestion of CBD-rich hemp extract in female and male rats, and the pattern of changes may be sex and tissue dependent.